B2 Harry Hope - NC Symposium Presentation (Final).pdf - Gill, Philip (Cranfield University, 2023)
Evaluation of a ‘Stabiliser Cocktail’ for a plasticised Nitrocellulose Polymer Bonded Explosive Harry Hope - AWE
Keywords: 'nitrocellulose'